Region-specific effects of blocking estrogen receptors on longitudinal bone growth. Issue 1 (16th June 2021) - Jin, Lin-Yu; Lv, Zhen-Dong; Su, Xin-Jin; Xu, Shuai; Liu, Hai-Ying; Li, Xin-Feng
Abstract : Estrogen receptors (ERs) regulate the development of the growth plate (GP) by binding to estrogen, a phenomenon that determines the growth of skeletal bone. However, the exact mechanisms underlying the regulatory effects of ERs on axial and appendicular growth plates during puberty remain unclear. In the present study, the strategy of ERβ blocking resulted in increased longitudinal elongation of the appendicular bone ( P < 0.01), whereas ERα blocking suppressed appendicular elongation ( P < 0.05). Blocking both ERs did not have opposite effects on axial longitudinal growth. The expression of chondrocyte proliferation genes including collagen II, aggrecan, and Sox9 and hypertrophic marker genes including collagen X, MMP13, and Runx2 was significantly increased in the growth plate of female mice treated with ERβ antagonist compared with that in the GP of control mice ( P < 0.05). There were no significant differences in local insulin-like growth factor 1 (IGF-1) expression among these groups ( P > 0.05), and Indian hedgehog protein (Ihh) and parathyroid-related protein (PTHrP) expressions differed among these groups ( P < 0.05). ERs appeared not to affect axial bone growth during puberty in female mice ( P > 0.05). Our data show that the blocking of different ER subtypes might have a region-specific influence on longitudinal appendicular and axial growth.